2005
DOI: 10.1002/bjs.4803
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double-blind trial of laparoscopic Nissen fundoplication versus anterior partial fundoplication

Abstract: Nissen fundoplication cured reflux in all patients up to 2 years, but 5 per cent required revisional surgery. Recurrent reflux was more common after anterior fundoplication, but dysphagia was rare. Patient satisfaction was excellent in both groups. Revisional laparoscopic surgery was safe and usually successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
3
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 18 publications
8
103
3
3
Order By: Relevance
“…12 However, the principal investigator of the South African trial worked with the Australian research group during the first trial, and then applied identical surgical techniques and questionnaires in the South African patient population. 12 The only difference in data collection was that the use of antisecretory medication was not assessed in the South African trial. 12 Another limitation is that we relied on clinical follow-up using validated questionnaires and we did not repeat pH monitoring, esophageal manometry or endoscopy at 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 However, the principal investigator of the South African trial worked with the Australian research group during the first trial, and then applied identical surgical techniques and questionnaires in the South African patient population. 12 The only difference in data collection was that the use of antisecretory medication was not assessed in the South African trial. 12 Another limitation is that we relied on clinical follow-up using validated questionnaires and we did not repeat pH monitoring, esophageal manometry or endoscopy at 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…12 The only difference in data collection was that the use of antisecretory medication was not assessed in the South African trial. 12 Another limitation is that we relied on clinical follow-up using validated questionnaires and we did not repeat pH monitoring, esophageal manometry or endoscopy at 5 years. Objective studies were undertaken at early follow-up in each trial, and the results have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past year, two RCTs 31,33 have been published comparing 180˚ LAF to LNF in addition to the three trials 30,32,34 that had been reported earlier, with 5-year results of two of these trials reported as well. 9,31 Some of these individual trials were inconclusive as they were underpowered, and hence too small to identify significant differences regarding the most important determinants of successful antireflux surgery: objective reflux control, dilatations for dysphagia and the need for surgical reintervention.…”
Section: Discussionmentioning
confidence: 99%
“…The principal investigators of the South African and Chinese RCT worked with the Australian research group during the first trial 34 and subsequently applied identical surgical techniques and questionnaires for their trials. 30,31 Consequently, a complete set of identical outcome measures and scales could be pooled. These 3 trials comprise 81% of the included patients and reported both one and five-year results.…”
Section: Discussionmentioning
confidence: 99%